2006
DOI: 10.1056/nejmoa060900
|View full text |Cite|
|
Sign up to set email alerts
|

Homocysteine Lowering with Folic Acid and B Vitamins in Vascular Disease

Abstract: Supplements combining folic acid and vitamins B6 and B12 did not reduce the risk of major cardiovascular events in patients with vascular disease. (ClinicalTrials.gov number, NCT00106886; Current Controlled Trials number, ISRCTN14017017.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
218
2
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,424 publications
(240 citation statements)
references
References 18 publications
7
218
2
3
Order By: Relevance
“…Recently, several large randomized studies showed that although homocysteine can be lowered, there is not necessarily a reduced risk of major cardiovascular events [16, 17, 29]. This raises the questions whether any benefit can be gained from lowering homocysteine and what role homocysteine actually plays in contributing towards cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several large randomized studies showed that although homocysteine can be lowered, there is not necessarily a reduced risk of major cardiovascular events [16, 17, 29]. This raises the questions whether any benefit can be gained from lowering homocysteine and what role homocysteine actually plays in contributing towards cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…Although supplementation with folic acid, B 6 and B 12 usually decreases homocysteine in patients with vascular disease [16, 17], it often remains elevated in ESRD patients despite supplementation of folic acid, B 6 and B 12 . Several studies have reported only moderate effects, even with very high doses of folic acid (up to 15 mg/daily) [18].…”
Section: Introductionmentioning
confidence: 99%
“…Of these, 2573 (61.8%) were subsequently enrolled in the WENBIT (Western Norway B‐vitamin Intervention Trial; NCT00354081) and received either (1) folic acid, vitamin B12 and vitamin B6 (n=642), (2) folic acid and vitamin B12 (n=642), (3) vitamin B6 (n=643), or (4) placebo (n=646) 14. Because B‐vitamin supplementation has been reported to lower the risk of stroke in some studies,15, 16 we excluded patients who received supplementation with B‐vitamins in the WENBIT. In addition, patients with missing baseline data on cystathionine and 1 patient with an extremely high cystathionine level (20 μmol/L) were excluded, leaving 2036 patients eligible for the current analyses (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, it can be suggested that lowering homocysteine levels with B12, B6 and folic acid would prevent cardiovascular events. However, in the three large prospective trials (VISP, HOPE-2 and NORVIT) in patients with established cardiovascular disease [10,11,12], there was no clinical benefit of treatment with folic acid and B vitamins for prevention of recurrent cardiovascular events and mortality. Although our population is a small group of 211 patients, the results are in accordance with the results of the three large studies.…”
Section: Discussionmentioning
confidence: 99%